2020
DOI: 10.1155/2020/6935724
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Prognostic Significance of Estrogen Receptorα(ERα), Estrogen Receptorβ(ERβ), and Human Epidermal Growth Factor Receptor 2 (HER-2) in Thyroid Carcinoma

Abstract: Purpose. The primary aim of this study was to determine the incidence of estrogen receptor α (ERα), estrogen receptor β (ERβ), and human epidermal growth factor receptor 2 (HER-2) expression in various subtypes of thyroid carcinoma (TC) of follicular origin and the secondary aim was to correlate the expression with various clinicopathologic prognostic factors. Methods. Immunohistochemistry analysis was performed on archival paraffin-embedded tissue sections (1991–2016). ERα, ERβ, and HER-2 expressions were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
4
6
1
3
Order By: Relevance
“…Notably, although our study investigated the regulating effects of CST1 on cancer progression and stemness in PTC, the detailed molecular mechanisms had not been elucidated. Previous data suggested that CST1 might regulate CSC properties in PTC via targeting ERβ [ 22 ], but the role of ERβ in regulating PTC malignancy was controversial, which played both tumor‐promoting [ 22 ] and ‐suppressing [ 36 , 37 ] roles in PTC. In addition, CST1 had also been reported to modulate the development of cancers via targeting multiple signaling pathways (PI3K, phosphatidylinositol 3‐kinase), such as ERα/PI3K/AKT/ERα loopback pathway [ 38 ], Wnt pathway [ 39 ] and so on, but future work was still needed to investigate the molecular mechanisms by which CST1 facilitated the development of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although our study investigated the regulating effects of CST1 on cancer progression and stemness in PTC, the detailed molecular mechanisms had not been elucidated. Previous data suggested that CST1 might regulate CSC properties in PTC via targeting ERβ [ 22 ], but the role of ERβ in regulating PTC malignancy was controversial, which played both tumor‐promoting [ 22 ] and ‐suppressing [ 36 , 37 ] roles in PTC. In addition, CST1 had also been reported to modulate the development of cancers via targeting multiple signaling pathways (PI3K, phosphatidylinositol 3‐kinase), such as ERα/PI3K/AKT/ERα loopback pathway [ 38 ], Wnt pathway [ 39 ] and so on, but future work was still needed to investigate the molecular mechanisms by which CST1 facilitated the development of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In this case report, the patient had a hormonal positive, stage IIB, but poorly differentiated IDC. BC-TC also share oestrogen receptor α (ERα), oestrogen receptor β (ERβ) and HER-2 expression and phosphatidylinositol 3-kinase pathway (PI3K) pathway activation [17]. ERα increases the proliferation rate of cancer cells, while ERβ is pro-apoptotic.…”
Section: Discussionmentioning
confidence: 99%
“…Serta didapatkan rerata nilai skor HER2 yang lebih tinggi pada kelompok dengan invasi kapsular dan tidak. [8][9][10][11] Namun, penelitian lebih lanjut dibutuhkan karena besarnya HER2 yang bernilai equivocal perlu dikorelasikan dan dilanjutkan dengan pemeriksaan FISH.…”
Section: Pembahasanunclassified
“…ER positif pada pasien usia tua dan grade yang rendah, tidak berhubungan dengan ekspresi HER2. 25 Mishra (2020) dan Dai (2017) menyatakan terdapat hubungan antara ekspresi HER2 dan ER dengan faktor prognosa PTC seperti ukuran tumor dan invasi kapsular. Namun, penelitian tersebut tidak menyebutkan profil usia sampel terbanyak.…”
Section: Pembahasanunclassified
See 1 more Smart Citation